2002
DOI: 10.1016/s0925-4439(01)00093-x
|View full text |Cite
|
Sign up to set email alerts
|

Sialyltransferase activity of human plasma and aortic intima is enhanced in atherosclerosis

Abstract: Sialyltransferase activity has been determined in membrane preparations containing the Golgi apparatus that were isolated from atherosclerotic and normal human aortic intima as well as in plasma of patients with documented atherosclerosis and healthy donors by measuring the transfer of N-acetylneuraminic acid (NeuAc) from CMP-NeuAc to asialofetuin. The asialofetuin sialyltransferase activity was found to be 2 times higher in the atherosclerotic intima as compared to the normal intima and 2-fold higher in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Previous studies have indicated that serum TSA concentrations are elevated in diabetes mellitus (both type 1 and type 2) with and without vascular complications (12). It is worth mentioning that a (37) reported elevated activity of sialyl transferase in aortic intimal and plasma in atherosclerosis. Since, sialyl transferase involves in different metabolic pathways for adding sialic acid to glycoproteins and glycolipids (12).…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have indicated that serum TSA concentrations are elevated in diabetes mellitus (both type 1 and type 2) with and without vascular complications (12). It is worth mentioning that a (37) reported elevated activity of sialyl transferase in aortic intimal and plasma in atherosclerosis. Since, sialyl transferase involves in different metabolic pathways for adding sialic acid to glycoproteins and glycolipids (12).…”
Section: Discussionmentioning
confidence: 92%
“…It has long been known that changes in the level of circulatory ST6Gal-1 and the circulatory sialyl-glycan structures constructed by ST6Gal-1 are associated with a diverse array of clinical conditions including stress (6), atherosclerosis(4, 34), alcoholism (35, 36), as well as in a certain cancers, particularly colon, breast cancers and multiple myeloma (1012). Studies in the 1980's have established that elevated release of ST6Gal-1 into the blood was a component of the hepatic acute phase response (37, 38), although insight into the physiologic contribution of blood ST6Gal-1 remained largely elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Glycotransferases including sialyltransferases may also be expressed on cell surfaces2728. With respect to the vascular wall, sialyltransferase activity has been observed in membrane preparations containing the Golgi apparatus isolated from human aortic intima29. Expression of ST6GALNAC5 in murine (accession numbers in EMBI-EBI (http://www.ebi.ac.uk/expressionprofiler/): E-GEOD-775, E-GEOD-1479, and E-GEOD-24940) and human (E-GEOD-2240, E-GEOD-40231) heart cells, including human coronary artery cells (E-GEOD-3526), has been shown in several microarray experiments17.…”
Section: Discussionmentioning
confidence: 99%